Knowledge, confidence, and clinical experience of physiotherapists and multiprofessional team on pulmonary rehabilitation - Isabella Diniz Faria; Liliane Patrícia de Souza Mendes; Renata de Carvalho Schettino; Bianca Louise Carmona Rocha; Jennifer A. Alison; Marcelo Velloso (Universidade de São Paulo, 2024)
ABSTRACT The knowledge deficit of health professionals has been a barrier to expanding and implementing of pulmonary rehabilitation (PR) services, despite the reported benefits of PR for individuals with Chronic Respiratory Disease (CRD). This study aims to assess the preparedness of health care professionals from two Brazilian cities to perform PR in the public health system. This is survey is part of a larger project to implement PR in the Brazilian public health system. A self-administered questionnaire was used to assess the knowledge (19 questions), training (7 questions), confidence (10 questions), and clinical experience (8 questions) of physical therapists (PT) and the multiprofessional team (MT) before a PR workshop. In total, 44 PT and 231 MT answered the questionnaire. The mean total knowledge score was 10±3 for PT and 6±3 for MT. Few physical therapist reported having "a lot" of experience (25%) and confidence (22.7%) to perform PR, as well as sufficient training to conduct the six-minute walk test (27.3%).Even fewer MT reported having "a lot" of experience (10%) and sufficient training (4.8%) to perform PR, as well as to plan the educational program for patients (10%) and the confidence to refer patients to PR (6.5%). This is the first study to evaluate the preparedness of professionals from the Brazilian public health network to provide PR. Notably, both PT and MT have low preparation to perform PR in the studied cities, reinforcing the need for continuing education.